Rozmowy o wartościach. Dyskusje młodzieży na łamach „Sztandaru Młodych” 1950–1956 - Mazur, Mariusz (Pamięć i Sprawiedliwość, 2011)
While it is true to say that the existence of discussions in the “Sztandar Młodych” magazine might suggested moving towards democracy and pluralism in opinions, in fact these conversations imposed particular ways of thinking, conviction about indisputability of various axioms and behaviour patterns. Theiraim was to determine one proper interpretation of official ideas, including particular behaviours, aspirations, beliefs and attitudes, which mainly was: restoring the traditional patterns and also building new construction. What is more, they were based on a new ideology and propaganda and on old cultural moulds. Twocategories of discourses could be there distinguished: authoritarian and universal narratives. During those discussions, such standards as: subordinating to particular ideology, dependency-domination relations, hierarchy and collectivism tookon a new significance. A total devotion and submissiveness to the authority were considered to be real values. Moreover, significant aspects like heroism of friendship and love, depending on ideological attitudes, were widely discussed. The ideological factor was dominating in argumentation concerning women’s work in professions hitherto considered to be masculine. There were also some discussions concerning universal topics such as: social politeness, relations between the young and the elderly and spectators’ behaviour on football stadiums. Ideologicalindoctrination interlaced with demonstrating basic needs and with issues that young people, regardless of their political convictions, were interested in.